Nuclear endonuclease G controls cell proliferation in ovarian cancer - Ye Na Choi; Tae Woong Seo; Yui Taek Lee; Dar Heum Jeong; Soon Ji Yoo (FEBS Open Bio, 2023)
Ovarian cancer is characterized by a high degree of genetic heterogeneity. Platinum‐based chemotherapy and some gene‐targeted therapies have shown limited treatment efficacy due to toxicity and recurrence, and thus, it is essential to identify additional therapeutic targets based on an understanding of the pathological mechanism. Here, we report that endonuclease G, which exhibits altered expression in ovarian cancer, does not function as a cell death effector that digests chromosomal DNA in ovarian cancer. Endonuclease G is modulated by intracellular reactive oxygen species dynamics and plays a role in cell proliferation in ovarian cancer, suggesting that targeting endonuclease G alone or in combination with other antitumor agents may have the potential for development into a treatment for endonuclease G‐overexpressing cancers, including ovarian cancer.